Mathematical Formulas in Text to Speech System - Peter Caky; Juraj Boron; Martin Klimo; Katarina Bachrata (Communications - Scientific letters of the University of Zilina, 2009)
A modular based system for synthesis of a written text allows solving partial problems separately. If there is designed a logical structure with clear interfaces, it could be possible to prepare modules for variant processes by different members of the team, without necessity of the coordinated work. The paper deals with amodule for engine reading of mathematical formulas in aSlovak text-to-speech system. The problem consists in the conversion of formulas to the written text in Slovak language and consequently additional conversion to the phonetic form. The main idea is to use the markup language LaTeX.